Moon Fall: The Starless Crown - Book 1 - Rollins, James, 1961- (New York : Tor, 2022)
"A gifted student foretells an apocalypse. Her reward is a sentence of death. Fleeing into the unknown she is drawn into a team of outcasts: a broken soldier, who once again takes up the weapons he's forbidden to wield and carves a trail back home. A drunken prince, who steps out from his beloved brother's shadow and claims a purpose of his own. An imprisoned thief, who escapes the crushing dark and discovers a gleaming artifact--one that will ignite a power struggle across the globe. On the run, hunted by enemies old and new, they must learn to trust each other in order to survive in a world evolved in strange, beautiful, and deadly ways, and uncover ancient secrets that hold the key to their salvation"--
Keywords: Apocalypse -- Fiction; Outcasts -- Fiction; Fantasy fiction; Thrillers (Fiction)